Japanese Loanwords for Literature and Writing in Current Spanish - Fernández Mata, Rafael (2018)
Japanese loanwords related to Literature and writing constitute the sixth biggest semantic field (6 words out of a total of 92) of all such words used currently in Spanish. For the first time concerning Spanish, the Literature and writing Japanese loanwords are described thoroughly from a formal, semantic and historical perspective in the present article. Further, the degree of adaptation of these loanwords within the Spanish lexical inventory will be indicated.